DAMPAK TERMINAL MANGKANG KOTA SEMARANG DAN PERMASALAHAN DI KAWASAN SEKITARNYA STUDI KASUS : TERMINAL MANGKANG SEMARANG - Dyah Andriyanti; Rachmat Mudiyono (Universitas Islam Sultan Agung Semarang, 2017)
This study aims to determine the effect of the presence of terminal Mangkang Semarang to the problems in the surrounding area. In addition to the above-mentioned objectives of this research has the goal to identify Semarang city transportation management, transportation terminals Mangkang analysis, sera footprint analysis to find out the problems that arise, land use, and the use of function space. To achieve the goals and objectives of the research, the method of analysis used is descriptive qualitative analysis.Based on the analysis showed that the terminal performance is less effective and efficient impact on the problems in the surrounding area that the transportation problems in front Mangkang terminal form of congestion caused by transport stops outside the terminal, use less maksmial kiosks that appear hawkers, and environmental problems in the area of the terminal. From the analysis carried out resulted in a recommendation that is used as an alternative in solving problems encountered in general in the terminal region Mangang related to transportation management, transportation terminals, and terminal area footprint. Keywords : Transportation, Terminal, Regional development.